Mathematical and computational models - Nadarajan, R. ([S.l.] : Narosa Pub House, 2008)
The ability to construct a mathematical model for solving complex problems is an art. Computational models enable the study of complex dynamic problems in the real world. Mathematical and Computational Models provides an in-depth review of original research articles in the field of Stochastic Models and Optimization Techniques, Graph Theory, Soft Computing, Theoretical Computer Science, Cryptography and Security in Computing It is an interdisciplinary field of academic study which aims at modeling natural, biological and engineering research problems. It will be of great interest and use to researchers and scientists in various fields.